(untitled) (International Journal of Engineering and Computer Science, 2017)
Millions of naira is been lost annually in organizations across Nigeria as a result of poor services been rendered to various clients in organizations, this is due to the facts that proper attendance management system is not in place in various organizations across the country. The management of staff’s attendance record daily has become a difficult challenge. The effort required in generating monthly report and also knowing the cumulative numbers of staffs has become a major task as manual assessment produces errors, and also it is time consuming. For the stated reason, an effective electronic staff attendance system using fingerprint is introduced in this work. This system will take attendance electronically with the aid of a fingerprint scanner (fingerprint device) and the attendance records are stored in the application storage unit (database). Attendance is marked after staff identification. For identification of staff, a fingerprint scanner is used. This process eradicates the need for stationary materials for record keeping; this will eliminate the issues of impersonation. This paper proposes the use of fingerprint biometric system to eliminate the problem being faced by traditional paper and pencil attendance register being provided in organizations.